2023
DOI: 10.3389/fsurg.2022.1079120
|View full text |Cite
|
Sign up to set email alerts
|

Femoral and tibial cementless fixation neither increases blood loss nor impedes early functional recovery: A randomized controlled trial

Abstract: BackgroundWhether cementless fixation on femoral and tibial components increases blood loss during total knee arthroplasty (TKA) is unclear. The purpose of this randomized controlled trial was to compare blood loss and early functional recovery between patients who underwent cementless or cemented TKA.MethodsBetween November 2021 and April 2022, sixty-one eligible patients at our medical center were randomized to cementless and cemented group. The primary outcome was total blood loss (TBL). Secondary outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, the literature on intraoperative and perioperative blood loss has been inconsistent. Some studies show no difference 118,128,129 while others suggest higher blood loss with cementless TKAs 130,131 . It is thought that cementation may tamponade bleeding 44 .…”
Section: Advantages Disadvantages and Considerationsmentioning
confidence: 99%
“…However, the literature on intraoperative and perioperative blood loss has been inconsistent. Some studies show no difference 118,128,129 while others suggest higher blood loss with cementless TKAs 130,131 . It is thought that cementation may tamponade bleeding 44 .…”
Section: Advantages Disadvantages and Considerationsmentioning
confidence: 99%
“…Studies involving early-generation porous-coated anatomic TKA, patients aged 55 years or younger, and simultaneous cemented and cementless TKA in the same patient for both knees have also indicated higher blood loss with cementless TKA [ 13 , 14 , 15 , 21 ]. However, recent studies using newer-generation cementless prostheses have reported comparable blood loss to cemented TKA in terms of drainage volume [ 22 ], estimated blood loss [ 18 , 23 ], and intraoperative bleeding [ 24 ]. On the other hand, one study using a modern cementless prosthesis estimated more intra-articular bleeding with cementless TKA based on the difference in drain reduction after tranexamic acid application.…”
Section: Discussionmentioning
confidence: 99%
“…This different result can be attributed to differences in PBM protocol, such as the dose/route of TXA administration, presence of drain clamping, and transfusion trigger. In addition, advancements in prostheses and surgical techniques may have contributed to these outcomes [ 17 , 18 ]. We demonstrate that SB TKA with newer-generation cementless implant did not increase blood loss nor transfusion rate in patients receiving contemporary strict PBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation